PEMBERDAYAAN PEREMPUAN OLEH LEMBAGA PEMBERDAYAAN EKONOMI DAN SOSIAL MASYARAKAT (LPESM) DI DESA TEMUSAI KECAMATAN BUNGA RAYA KABUPATEN SIAK - Henmifa Nabila Sari; Yoskar Kadarisman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Women are an integral part of a society, including in poor communities. Women have the same potential as men to contribute to community development. But in reality, women are still not given a more role, even marginalized. Non-governmental organizations such as LPESM as one of the important elements in society that can help realize women’s empowerment. In essence poverty can start from low access to education causes low economic access. Which ultimately leads to poverty. Socialization is carried out that people are more enthusiastic about developing their business and preserving the environtment so that it remains green. This study uses a descriptive qualitative research method. Data collection was carried out in this study in the form of diract observation, in-depth interviews, and documentation. In conducting interviews, the informants were members of LPESM. Interpretation of data is carried out in stages starting from data collection, data reduction to conclusions. And the results of research that can be an alternative for villagers who want to develop ther businesses. And the inhibiting factors of LPESM in carrying mindsets and the difficulty of finding free time for housewives. Keywords: Women’s Empowerment, institution, role